2013
DOI: 10.1080/13854046.2013.845246
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Survey on Rotated Drawing in Persons With Mild Cognitive Impairment or Degenerative Dementia

Abstract: Rotation of drawings has been described in focal brain lesions, at copy when the dorsal visual stream is involved, at recall in patients with memory or frontal dysfunction. In the present study Rey-Osterrieth Complex Figure performance was reviewed in 445 consecutive patients with mild cognitive impairment or degenerative dementia; a smaller sample (n = 243) had also performed the recall trial. Rotation was present in 19 cases overall: at copy in 11, at recall in 7, and at recall on a first assessment and at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Behaviorally, beside impairments of constructional abilities, the neuropsychological profile comprised deficits of visual attention and executive functions. These patterns are in line with previous reports on patients with degenerative disorders and Mild Cognitive Impairment [ 2 , 3 ]. Critically, patient DDA exhibited network-specific hyper-connectivity of the undamaged (i.e., left) hemisphere within the DAN (i) and frontoparietal executive-control (ii) networks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Behaviorally, beside impairments of constructional abilities, the neuropsychological profile comprised deficits of visual attention and executive functions. These patterns are in line with previous reports on patients with degenerative disorders and Mild Cognitive Impairment [ 2 , 3 ]. Critically, patient DDA exhibited network-specific hyper-connectivity of the undamaged (i.e., left) hemisphere within the DAN (i) and frontoparietal executive-control (ii) networks.…”
Section: Discussionsupporting
confidence: 93%
“…Rotated drawing is a constructional phenomenon in which when coping or recalling from memory a complex figure, the model is reproduced rotated of ± 90° or 180°, although spatial relationships among basic elements are preserved [ 1 ]. Rotation has been reported in several clinical cohorts such as neurodegenerative [ 2 ] and stroke [ 3 ] patients, with a slightly higher frequency after right hemisphere lesion. Previous neuroimaging findings [ 2 , 3 ] indicated that rotation on copy is related to dysfunctional activity in parietal regions belonging to the so-called dorsal attention network (DAN) involved in control of the visuospatial attention [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study on a large sample of patients with MCI or degenerative dementia who underwent copy and recall of the ROCF, Isella et al [182] observed rotation on the copy condition in 2.7% patients and on recall in 3.3% patients. In a subsequent prospective study on a mixed sample of patients with degenerative dementias or focal brain lesions, rotation at the copy of the ROCF was associated with visuospatial and selective attention impairments, and with more severe temporo-parietooccipital atrophy or hypometabolism, whereas no specific profile of cognitive impairment distinguished patients with rotation at recall of the ROCF, in whom frontal abnormalities were more frequent [183].…”
Section: Rotationmentioning
confidence: 99%
“…ROCFT is classically used in dementia and mild cognitive impairment (11). It has been reported that the addition of a nonverbal memory and executive functioning test, such as ROCFT, to the standard mini-mental state examination could improve the detection of mild cognitive impairment (12).…”
Section: Introductionmentioning
confidence: 99%